Insect repellent activity of medicinal plant oils against aedes aegypti (LINN.), anopheles minimus (Theobald) and culex quinquefasciatus say based on protection time and biting rate - Phasomkusolsil, Siriporn; Soonwera, Mayura (My University, 2010)
This study investigated insect bite protection and length of the protection with 30 repellents which were divided into 3 categories: plant oil, essential oil and essential oil with ethyl alcohol, tested against three mosquito species, Aedes aegypti, Anopheles minimus and Culex quinquefasciatus, under laboratory conditions. The plant oil group was comprised of Phlai (Zingiber cassumunar) and Sweet basil (Ocimum basilicum). Both substances were effective as repellents and feeding deterrents against An. minimus (205 minutes protection time and a biting rate of 0.9%), Cx. quinquefasciatus (165 minutes protection time and 0.9% biting rate) and Ae. aegypti (90 minutes protection time and 0.8% biting rate). Essential oil from citronella grass (Cymbopogon nardus) exhibited protection against biting from all 3 mosquito species: for An. minimus, Cx. quinquefasciatus and Ae. aegypti, the results were 130 minutes and 0.9%, 140 minutes and 0.8%, and 115 minutes and 0.8%, respectively. The period of protection time against Ae. aegypti for all repellent candidates tested was lower than the Thai Industrial Standards Institute (TISI) determined time of greater than 2 hours.
Keywords: Aedes aegypti; Anopheles minimus; Culex quinquefasciatus; Medicinal plant oil; Repellent activity